Nepal : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waivers for Nonobservance of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report, 2007)
The staff report for the Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PGRF) highlights Nepal's economic outcomes and macroeconomic policies. Financing needs and logistics of the peace process pose continuing challenges. Macroeconomic stability remains intact, but the speed of structural reform implementation has been slow. Macroeconomic policies remain anchored and the authorities are aware of the need for further structural reforms. Financial sector reforms can help improve intermediation and financial stability.